2005
DOI: 10.1507/endocrj.52.571
|View full text |Cite
|
Sign up to set email alerts
|

Hodgkin Lymphoma in Temporal Association with Growth Hormone Replacement

Abstract: Abstract. The association between growth hormone (GH) replacement and malignancy has long been debated. We report a case of Hodgkin lymphoma that developed in temporal association with the initiation of GH replacement in a 57-yearold woman with panhypopituitarism secondary to a non-secretory pituitary macroadenoma. Treatment of her pituitary tumor included transphenoidal surgery, external beam radiation, Bromocriptine and Cabergaline therapy. In addition to replacement steroid, thyroid and sex hormones, she in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Furthermore, we have previously observed that low pituitary GH levels were not associated with a recip-rocal decline in immunoreactive GH produced by lymphocytes during human aging (Luz et al 2006). The potential side--effects of long--term GH replacement shall be considered, and include carpal tunnel syndrome, arthralgia, increased risk for diabetes (as it increases insulin resistance) and it has been associated with increased risk for Hodkin's lymphoma (Freedman et al 2005).…”
Section: Gh and Ghrelin Replacement Therapiesmentioning
confidence: 99%
“…Furthermore, we have previously observed that low pituitary GH levels were not associated with a recip-rocal decline in immunoreactive GH produced by lymphocytes during human aging (Luz et al 2006). The potential side--effects of long--term GH replacement shall be considered, and include carpal tunnel syndrome, arthralgia, increased risk for diabetes (as it increases insulin resistance) and it has been associated with increased risk for Hodkin's lymphoma (Freedman et al 2005).…”
Section: Gh and Ghrelin Replacement Therapiesmentioning
confidence: 99%
“…It is obvious that a complex hormone that acts in the entire body in a myriad of systems will have important side effects (e.g., injection-site reaction joint swelling, joint pain, carpal tunnel syndrome, increased risk of diabetes) (Liu et al, 2007). Although rare, patients can sometimes produce an immune response against GH, and GH may also be a risk factor for Hodgkin's lymphoma (Freedman et al, 2005). Certainly, the complex biology of GH, the lack of clinical trials, and its side effects have limited its utilization for the treatment of sarcopenia.…”
Section: Growth Hormonementioning
confidence: 99%
“…Growth hormone is secreted under joint and coordinated control of three hypothalamus hormones: growth hormone-releasing hormone (GHRH). Somatostatin and Ghrelin (GHRH), GHRH and gerlin are positive regulators that stimulate growth hormone release [9]. Somatostatin (SST) is a negative regulator that inhibits the secretion of the hormone.…”
Section: Introductionmentioning
confidence: 99%